Microwave Assisted Synthesis of Barium Titanate Nanoparticles and Its Effects on the Proliferation of Primary Osteoblasts in vitro - Wang, Wenying; Zheng, Baofeng; Ma, Yanyan; Liu, Zhu; Li, Zhilin; Zhou, Guoqiang (Asian Journal of Chemistry, 2014)
The barium titanate nanoparticles were successfully synthesized using microwave synthesis method and evaluated for antiproliferation activity against primary osteoblasts. The effects of microwave irradiation power and reaction time on the reaction rate and size control of barium titanate nanoparticles were investigated. The data revealed that the nanoparticle size decreasesd with increasing irradiation power. The barium titanate nanoparticles were formed after 20 min of microwave irradiation. The barium titanate nanoparticles synthesized were analyzed by field emission scanning electron microscopy, powder X-ray diffraction, Fourier transform infrared spectroscopy and dynamic light scattering. The barium titanate nanoparticles were nearly spherical particles with an average size of 80-100 nm. The antiproliferation activity of barium titanate nanoparticles showed that the inhibition effects followed dose and time dependent manner. The inhibition effects were increased with decreasing size and the effects may be related to cell apoptosis mechanism.